Probing the symmetry of the potential of localized surface plasmon resonances with phase-shaped electron beams - Giulio Guzzinati (Nature Portfolio, 2017)
The sign of the field in plasmonic excitations cannot be accessed by direct measurements. Here Guzzinatiet al. overcome this limitation by shaping the wavefunction of an electron beam to match the symmetry of the plasmon’s charge symmetry, offering selective detection of specific plasmon modes.